Expression of human liver HSPGs on acute myeloid leukemia - Vongchan P. (2014)
Heparan sulfate proteoglycans (HSPGs) play important biological roles in cell-matrix adhesion processes and are essential regulators of growth actions. The expression of the different HSPGs in itself is tightly regulated providing strict controls on the activities of the bound ligands. Human liver is a target for a number of pathogens, and HSPGs have been demonstrated in several cases to play a pivotal role in infectivity. Despite HSPGs important biological functions, little is known about its cell-specific distribution patterns. Human liver HSPG was isolated, and a specific monoclonal antibody (mAb) 1E4-1C2 was produced. Distribution of HSPG reactive to this mAb was studied in normal blood cells, hematopoietic cell lines and blood cells isolated from patients with various hematologic disorders using indirect immunofluorescence. There was no expression of molecules recognized by this mAb on lymphoid (Daudi, Jurkat, SupT-1) and monocytoid (U937) cell lines. Peripheral blood cells, normal bone marrow, together with leukocytes isolated from patients with acute lymphoblastic leukemia, chronic myelocytic leukemia, Hodgkin's disease or Non-Hodgkin's lymphoma, were also negative. In contrast, 1E4-1C2 showed significant positive results on human myeloid cell lines HL-60 and K562. Moreover, it is interesting that this mAb also recognized epitopes on leukocytes isolated from acute myeloblastic leukemia. These results suggest that malignancies of cells in myeloid lineage may cause expression of HSPGs that are detected by this specific mAb, making it a potential co-marker for the diagnosis of acute myeloid leukemia.